Phytotherapy for Cachexia: Where Do We Stand? - Kuchta, Kenny; Cameron, Silke (Frontiers in Pharmacology, 2020)
In contrast to Western medicine, which currently offers no approved pharmacotherapy options for cachexia, in Japanese Kampo medicine multi-component extracts of medicinal plants are used with insurance coverage. For the traditional preparations Hochuekkito (補中益気湯), Juzentaihoto (十全大補湯), and Rikkunshito (六君子湯), multiple clinical research publications relate to cachexia. These preparations are also referred to as "Hozai" (補剤). A similar concept is found in Russian herbal medicine, where the term "Adaptogen" was coined for pharmacologically active substances which enhance adaptive stress repose. Hochuekkito showed efficacy in involuntary weight loss and fatigue in 63% of 162 patients with genitourinary cancer (Kuroda 1985). For cancer-related fatigue, a significant improvement was seen within 2 weeks (Jeong 2010). In patients with chronic fatigue syndrome, Hochuekkito showed an overall improvement with 8-12 weeks of therapy (Kuratsune 1997). In a randomized placebo-controlled trial on 13 geriatric patients in a 16 week treatment protocol, Hochuekkito showed a significant improvement of general health, physical functioning and the Profile of Mood States (POMS) (Satoh 2005). In 71 geriatric COPD patients in a placebo-controlled randomized study, Tatsumi (2009) found a significant body weight increase and a CRP, TNF-α, IL-6 decrease over 6 months of therapy. For Juzentaihoto in 48 hepatocellular carcinoma patients, Tsuchiya (2008) documented a significantly longer recurrence-free survival (49 vs. 24 months) as compared to the control group (p=0.023). For the much simpler Rikkunshito prescription, a retrospective study (Fujitsuka 2011) on 39 Stage III/IV pancreatic cancer patients treated with Gemcitabine (n=33) or Gemcitabine/Rikkunshito (n=6) showed a significantly prolonged median survival with 224 vs. 378.5 days (p<0.05). In an open-label clinical study (Utumi 2011) on geriatric cachexia in 6 dementia patients, treatment with Rikkunshito for 4 weeks resulted in a significant body weight increase. In all the above studies, the standardised dosage of 3x2.5 g/d for most Japanese health insurance-covered Kampo extract-preparations was applied. As there is currently no accepted pharmacotherapy option for cachexia available in the West, a transfer of these East Asian gold standard preparations into the European market would be desirable. More research in this field is urgently needed in order to provide new, effective treatments for cachexia patients.